Comparison of mid-term outcomes of carotid artery stenting for moderate versus critical stenosis - Veselka, Josef; Zimolová, Petra; Martinkovičová, Lucie; Tomašov, Pavol; Hájek, Petr; Malý, Martin; Spaček, Miloslav; Zemánek, David; Tesař, David (Archives of medical science, 2012)
INTRODUCTION: Little is known about the prognosis of moderate versus critical carotid stenosis treated by carotid artery stenting (CAS). MATERIAL AND METHODS: This was a retrospective analysis of a single-centre registry including 271 consecutive patients (69 ±9 years, 87% at high risk for surgery), in whom 308 procedures were performed. The study included both symptomatic (≥ 50% carotid artery stenosis) and asymptomatic (≥ 70% carotid artery stenosis) patients. The primary endpoint was the rate of adverse events during follow-up (range 1-48 months), defined as all-cause death or stroke. RESULTS: We treated 115 critical and 193 moderate stenoses and implanted 318 stents (56% with closed cell design). Embolic protection systems were used in 296 cases (96%). The technical success rate was 98.2% in the critical stenoses group and 99% in the moderate group (NS). During follow-up, the incidence of the primary endpoint was 12.9% (13 pts) in the critical stenoses group and 14.7% (25 pts) in the moderate stenoses group (estimated 3-year freedom from death/stroke was 0.844 vs. 0.812; log-rank test p = 0.983). Left ventricular ejection fraction < 40%, significant contralateral carotid artery occlusion or stenosis and renal insufficiency were identified as significant predictors of the primary endpoint (p < 0.03). CONCLUSIONS: Carotid artery stenting with embolic protection systems in patients at high risk for carotid endarterectomy is safe. Patients with initially moderate and critical stenoses have an identical mid-term prognosis with regard to death and stroke.
Keywords: follow-up; carotid stenosis; stenting